Delimitação do Embasamento da Bacia de Taubat - De Carvalho, Ancilla Maria Almeida; Vidal, Alexandre Campane; Kiang, Chang Hung [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2011)
The aim of this study is to define the basement map of the Taubaté Basin applying geostatistics to seismic, gravimetric and deep wells data. The study consisted of the interpretation of eleven seismic sections obtained in the central and northeastern portions of the basin. The altitude of the basement and the distribution of faults was determined based on these sections. New information was obtained from 79 wells located mainly in the regions of São José dos Campos and Jacareí. The method of kriging with an external drift was applied, using seismic and well data as the main variables and the gravimetric map as the secondary variable. The basement contour map obtained has a strong correlation with the main faults. It was possible to obtain a better resolution in the region of São José dos Campos and in the northeast area, where the vast majority of wells are located.
Basement delimitation of the Taubaté Basin
Keywords: Geostatistics; Seismics; Taubaté basin; basement rock; data interpretation; fault; geostatistics; kriging; seismic data; seismology; Brazil; Sao Jose dos Campos; Sao Paulo [Brazil]; Taubate Basin